(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In today’s digital era, social networks have evolved from being mere communication platforms into complex socio-psychological environments that shape individual identity, emotional well-being, and interpersonal relationships. Within this space, individuals are continuously engaged in social comparison, a phenomenon that often intensifies feelings of envy.